Hydrogen Peroxide Is Involved in Salicylic Acid-Elicited Rosmarinic Acid Production in Salvia miltiorrhiza Cell Cultures - Wenfang Hao; Hongbo Guo; Jingyi Zhang; Gege Hu; Yaqin Yao; Juane Dong (The Scientific World Journal)
Salicylic acid (SA) is an elicitor to induce the biosynthesis of secondary metabolites in plant cells. Hydrogen peroxide (H2O2) plays an important role as a key signaling molecule in response to various stimuli and is involved in the accumulation of secondary metabolites. However, the relationship between them is unclear and their synergetic functions on accumulation of secondary metabolites are unknown. In this paper, the roles of SA and H2O2 in rosmarinic acid (RA) production in Salvia miltiorrhiza cell cultures were investigated. The results showed that SA significantly enhanced H2O2 production, phenylalanine ammonia-lyase (PAL) activity, and RA accumulation. Exogenous H2O2 could also promote PAL activity and enhance RA production. If H2O2 production was inhibited by NADPH oxidase inhibitor (IMD) or scavenged by quencher (DMTU), RA accumulation would be blocked. These results indicated that H2O2 is secondary messenger for signal transduction, which can be induced by SA, significantly and promotes RA accumulation.